Impact of Parents' Educational Status on Infant Mortality in Wukari Local Government Area of Taraba State - Ojonugwa, Ameh Sunday; Shipurut, Geoffrey Nanbal; Damian, Gana Chuseh (International Journal of Education, Management, and Technology, 2025)
Infant survivability remains a critical public health concern, particularly in regions where access to healthcare and essential knowledge about child-rearing practices are limited. Parental education, especially for mothers, has been recognized as a vital tool in improving infant health outcomes. Educated parents are more likely to adopt healthy practices such as exclusive breastfeeding, immunization, and the early recognition of danger signs in infants. This study examines the impact of parents ‘educational status on infant mortality in Wukari Local government area of Taraba state. The paper used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 374,800 using the Tare Yamane formula. Questionnaires were distributed to 400 respondents who were randomly selected across the wards in Wukari LGA. Interviews were also conducted with six key informants to complement the data gathered from the questionnaires. Responses from the questionnaires were analyzed using descriptive statistics. Quantitative data were analyzed while outlining the key point presented by the key informant. The study revealed that Infant mortality rates are positively correlated with parents who have neither formal nor secondary education, indicating that low levels of education may be a contributing factor to lower infant health outcomes. The study recommended that increasing access to high-quality education, especially for women, through community programs and adult literacy initiatives is essential to giving parents the information they need to make better health decisions and take better care of their children.